TI_GERICHTE 11.2022.175 vom 20. März 2024 , Ipoteca legale degli artigiani e imprenditori: iscrizione definitiva - TI Tribunale d'appello (2024)
Ipoteca legale degli artigiani e imprenditori: iscrizione definitiva